Strong polarization-controlled terahertz generation by bi-elliptical polarized laser fields - Liu, Yan-Mei; Li, Ya-Ning; Zhang, Lei; Jiao, Zhi-Hong; Zhao, Song-Feng; Wang, Guo-Li (Frontiers in Physics, 2023)
Terahertz generation from atoms driven by two color linearly polarized (LP) and circularly polarized (CP) laser fields have been well investigated. In this work, based on the photocurrent model, we investigate theoretically the intensity and polarization characteristics of terahertz waves radiated by the bi-elliptical polarized two-color laser fields with orthogonal or parallel major axes. We show that polarization-controlled, including circularly polarized terahertz waves with sufficient intensity comparable to that of co-rotating CP or parallel LP laser field, can be generated by using a longerwavelength few-cycle bi-elliptical field. Our simulations also show that THz energy and ellipticity can be dramatically improved with dual-color elliptical field with tiny or large ellipticity, compared with that with two-color orthogonal LP field and counter-rotating CP laser field, respectively. Bi-elliptical polarized laser field provides a huge parameter space allowing for far-reaching control of THz emission.